Plasmodium vivax Reticulocyte Binding Proteins for invasion into reticulocytes - Chan, Li‐Jin (Cell Microbiol, 2019)
Plasmodium vivax is responsible for most of the malaria infections outside Africa and is currently the predominant malaria parasite in countries under elimination programs. P. vivax preferentially enters young red cells called reticulocytes. Advances in understanding the molecular and cellular mechanisms of entry are hampered by the inability to grow large numbers of P. vivax parasites in a long‐term in vitro culture. Recent progress in understanding the biology of the P. vivax Reticulocyte Binding Protein (PvRBPs) family of invasion ligands has led to the identification of a new invasion pathway into reticulocytes, an understanding of their structural architecture and PvRBPs as targets of the protective immune response to P. vivax infection. This review summarises current knowledge on the role of reticulocytes in P. vivax infection, the function of the PvRBP family of proteins in generating an immune response in human populations, and the characterization of anti‐PvRBP antibodies in blocking parasite invasion.